Environmental policies under debt constraint - Fodha, Mouez; Seegmuller, Thomas (Marseille, 2014)
"This article analyzes the consequences of environmental tax policies when the government imposes a constraint on stabilizing public debt. A public sector of pollution abatement is financed by taxation and by issuing public debt. Considering a simple overlapping-generations model, the tax reform stimulates steady-state investment. Then, the environmental quality and the aggregate consumption increase if and only if (i) pollution abatement is large enough and (ii) there is under-accumulation of the per capita capital stock. This arises if environmental taxation allows a decrease of either income taxation or debt-output ratio."